Terahertz spectroscopy for food diagnostic application - Toh, Jia Min (2018)
Due to the various food scandals and food mishandling in the past, there is an increasing demand for food safety. While there are many methods which can analyse the freshness of food, many are either too time consuming, costly or complicated. Coupled with the rise in demand for seafood in the recent years, there is an increasing need to come up with a more efficient, cost effective and accurate way to determine freshness of the food, particularly seafood. Terahertz technology is a viable option. With the advancement in Terahertz Technology, this technology has proven its usefulness in many applications such as identifying homogeneous and optically flat sample such as drugs in a fast and cost-effective manner. However, little studies were done to study meat, a complicated and non- homogeneous biological organism. Therefore, Terahertz Time Domain spectroscopy was used to study the freshness of salmon and three other fishes in both transmission and reflection mode in this project. The time domain result was then Fast Fourier Transformed and further analysed in Origin Lab to obtain the frequency dependent and material dependent parameters to determine the quality of the fish. Even though the results from reflection mode may not be as accurate as that of transmission mode, the freshness of a fish can be determined from the results obtained from both transmission and reflection mode. This project indicates the potential use of Terahertz technology as a fast and economical means to determine the freshness of the food.